An Analytical Study on the Development of the Concept of Integration of Science and Islam in IAIN Syekh Nurjati Cirebon - Septi Gumiandari; Ilman Nafi'a; Ahmad Asmuni (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2020)
The extensive mandate of the ministry of religious affaires to manage various non-religious majors has demanded Islamic higher educations to have each distinctive scientific building in the process of formulating the integration of science and religion. This study aims to analyze the development of the concept of integration of science and Islam that has been formulated in the IAIN Cirebon. Qualitative research with literature study showed the existence of the Muhsin Sejati concept was taken as a scientific integration icon, along with several other derived concepts, such as Jembatan Ilmu, the complementary inclusive paradigm, mata ilmu and blended theory. Unfortunately, the theorization of the concept of integration did not develop significantly, stagged in 2015. This was because the concept of Muhsin Sejati and its derivatives had not been legally ratified formally in Rector’s policy, nor was it followed up on the cabinet leadership policy afterwards. Besides scientific exclusivity, thought, personal background and primordialism still dominate in the campus atmosphere.